The spleen of Sonali chicken: morphohistology and biometric analysis at post hatching ages (Asian Journal of Medical and Biological Research, 2021)
Although Sonali chicken is introduced to the poultry industry of Bangladesh during 1999-2000 and after that playing a pivotal role in national economy, no literature is available regarding histomorphometry of spleen of Sonali chicken. As spleen is a key component of chicken’s defense mechanism, the study was designed to investigate the age related development of spleen of Sonali chicken, i.e, morphohistology and biometry at several postnatal stages. The investigation was carried out on 25 healthy Sonali chickens representing different ages at after hacting days 1, 14, 28, 42, and 56 (n=5). After ethically sacrifice (cervical subluxation method), spleen was collected and subjected for both macro and microscopic examinations. Haematoxylin and Eosin stain was done for the later. Morphologically, spleen was found lying dorsally at the right side of the abdominal cavity. It was oval or rounded organ, reddish brown in color. The gross morphometric observations (average weight, organ index, length, width and thickness) found significantly increasing throughout the tenure (p